2014
DOI: 10.4238/2014.december.19.22
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the full-length Hsp90 gene from Matricaria recutita

Abstract: ABSTRACT. Heat shock protein 90 (Hsp90) is one of the most abundant and conserved chaperone proteins and plays important roles in plant growth and responses to environmental stimuli. However, little is known regarding the sequence and function of Hsp90s in Matricaria recutita. In the present study, we cloned the full-length cDNA sequence of the hsp90 gene from this species. Using rapid amplification of cDNA ends technologies with 2 degenerate primers that were designed based on the hsp90 gene sequence from oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Many studies on the effects of tonsillectomy on the immune demonstrate discordant results. Some studies indicated that tonsillectomy decreases the serum immunoglobulin level during some or all of their follow-up periods[ 14 , 27 30 ] or alters cellular immunity[ 31 ]. In contrast, some studies reveal that tonsillectomies do not alter immune functions [ 15 , 17 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on the effects of tonsillectomy on the immune demonstrate discordant results. Some studies indicated that tonsillectomy decreases the serum immunoglobulin level during some or all of their follow-up periods[ 14 , 27 30 ] or alters cellular immunity[ 31 ]. In contrast, some studies reveal that tonsillectomies do not alter immune functions [ 15 , 17 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…ER-sHSP has the functional activity of a molecular chaperone (Zhao et al, 2007;Mamedov and Shono, 2008) and its overexpression can alleviate ER stress caused by tunicamycin and DTT exposure (Zhao et al, 2007). The aim of this study was to determine whether the constitutive expression of ER-sHSP would improve the abiotic tolerance of plants, as does overexpression of BiP (Alvim et al, 2001;Valente et al, 2009) and an increased HSP90 level (Ling et al, 2014). To this end, we examined salt tolerance in transgenic tomato plants expressing ER-sHSP.…”
Section: Introductionmentioning
confidence: 99%